Constrained inefficiency in GEI: A geometric argument - Mario Tirelli (Brown University, Department of Economics, 2005)
In this paper we use global analysis to study the welfare properties of general equilibrium economies with incomplete markets (GEI). Our main result is to show that constrained Pareto optimal equilibria are contained in a linear submanifold of the equilibrium set. This result is explicitly derived for economies with real assets, of which real numeraire assets are a special case.
Keywords: D52; D61; D62; 330; General equilibrium; incomplete markets; optimality; global analysis; Allgemeines Gleichgewicht; Unvollkommener Markt; Pareto-Optimum; Finanzinnovation; Theorie